2020
DOI: 10.1242/dmm.043174
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model to study retinitis pigmentosa pathology associated with mutations in the core splicing factor Prp8

Abstract: Retinitis pigmentosa (RP) represents genetically heterogeneous and clinically variable disease characterized by progressive degeneration of photoreceptors resulting in a gradual loss of vision. The autosomal dominant RP type 13 (RP13) has been linked to the malfunction of PRPF8, an essential component of the spliceosome. Over 20 different RP-associated PRPF8 mutations have been identified in human patients. However, the cellular and molecular consequences of their expression in vivo in specific tissue contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…The following Drosophila melanogaster strains were used: w 1118 (BDSC; RRID:BDSC_3605 ), ecd 1 ( 32 ), ecd Δ (this study), w;; FRT2A (BDSC; RRID:BDSC_1997 ), w;; FRT82B (BDSC; RRID:BDSC_2035 ), w; nubbin-Gal4, UAS-myr-mRFP ( nub>mRFP , this study), w; escargot-Gal4, UAS-GFP, tub-Gal80 TS ( esg TS > , 33 ), w; nubbin-Gal4, UAS-myr-mRFP; tub-Gal80 TS ( nub TS >mRFP , this study), w;; ecd l( 3 )23 FRT2A ( 22 ), w;; ecd Δ FRT2A (recombined in this study), w; UAS-ecd RNAi ( 22 ), w; UAS-prp8 RNAi (VDRC; ID18565), w;; UAS-Prp8 wt ( 34 ) , w;; UAS-SmD3::3xHA (FlyORF; F003987), w;; UAS - SmD3::3xHA, UAS-ecd RNAi (recombined in this study) , w; nubbin-Gal4, UAS-myr-mRFP; UAS - SmD3::3xHA, tub-Gal80 TS (this study) , w; nubbin-Gal4, UAS-myr-mRFP; ecd 1 (this study), w;; UAS - SmD3::3xHA, UAS-Prp8 wt (recombined in this study), w;; UAS - SmD3::3xHA, UAS-ecd RNAi , UAS-Prp8 wt (recombined in this study), eyFLP; act>y + >Gal4, UAS-GFP; FRT82B, tub-Gal80 ( 35 ), eyFLP; act>y + >Gal4, UAS-GFP; tub-Gal80, FRT2A (this study), w; UAS-Ecd wt ; FRT82B (this study) , w; UAS-Myc::Ecd TripleA ; FRT82B (this study), w; UAS-Myc::Ecd Δ 34 ; FRT82B (this study), w; UAS-Ecd wt ; ecd Δ FRT2A (this study), w; UAS-Myc::Ecd TripleA ; ecd Δ FRT2A (this study), w; UAS-Myc::Ecd Δ 34 ; ecd Δ FRT2A (this study). Details on Drosophila strains are described in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The following Drosophila melanogaster strains were used: w 1118 (BDSC; RRID:BDSC_3605 ), ecd 1 ( 32 ), ecd Δ (this study), w;; FRT2A (BDSC; RRID:BDSC_1997 ), w;; FRT82B (BDSC; RRID:BDSC_2035 ), w; nubbin-Gal4, UAS-myr-mRFP ( nub>mRFP , this study), w; escargot-Gal4, UAS-GFP, tub-Gal80 TS ( esg TS > , 33 ), w; nubbin-Gal4, UAS-myr-mRFP; tub-Gal80 TS ( nub TS >mRFP , this study), w;; ecd l( 3 )23 FRT2A ( 22 ), w;; ecd Δ FRT2A (recombined in this study), w; UAS-ecd RNAi ( 22 ), w; UAS-prp8 RNAi (VDRC; ID18565), w;; UAS-Prp8 wt ( 34 ) , w;; UAS-SmD3::3xHA (FlyORF; F003987), w;; UAS - SmD3::3xHA, UAS-ecd RNAi (recombined in this study) , w; nubbin-Gal4, UAS-myr-mRFP; UAS - SmD3::3xHA, tub-Gal80 TS (this study) , w; nubbin-Gal4, UAS-myr-mRFP; ecd 1 (this study), w;; UAS - SmD3::3xHA, UAS-Prp8 wt (recombined in this study), w;; UAS - SmD3::3xHA, UAS-ecd RNAi , UAS-Prp8 wt (recombined in this study), eyFLP; act>y + >Gal4, UAS-GFP; FRT82B, tub-Gal80 ( 35 ), eyFLP; act>y + >Gal4, UAS-GFP; tub-Gal80, FRT2A (this study), w; UAS-Ecd wt ; FRT82B (this study) , w; UAS-Myc::Ecd TripleA ; FRT82B (this study), w; UAS-Myc::Ecd Δ 34 ; FRT82B (this study), w; UAS-Ecd wt ; ecd Δ FRT2A (this study), w; UAS-Myc::Ecd TripleA ; ecd Δ FRT2A (this study), w; UAS-Myc::Ecd Δ 34 ; ecd Δ FRT2A (this study). Details on Drosophila strains are described in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 81%
“…Samples were resolved on 10% or 12% SDS-PAGE. Candidate proteins were detected by immunoblotting with primary antibodies: rabbit anti-dPrp8-CTD (1:1000, 34 ), rat-anti Ecd N-term (1:1000, 22 ), mouse anti-Flag M2 (1:1000, Sigma-Aldrich Cat# F1804, RRID:AB_262044 ), rabbit anti-Myc (1:2000, Cell Signaling Technology Cat# 2272, RRID:AB_10692100 ), rabbit anti-HA (1:2000, Abcam Cat# ab9110, RRID:AB_307019 ), mouse anti-ATP5α (1:2000, Abcam Cat# ab14748, RRID:AB_301447 ), rabbit anti-RFP (1:1000, MBL Cat# PM005, RRID:AB_591279 ), rabbit anti-GFP (1:2000, Acris Cat# TP401, RRID:AB_10013661 ) followed by incubation with corresponding goat anti-mouse (1:5000, Jackson ImmunoResearch Labs Cat# 715-035-150, RRID:AB_2340770 ), rabbit (1:5000, Jackson ImmunoResearch Labs Cat# 711-035-152, RRID:AB_10015282 ) and rat (1:5000, Jackson ImmunoResearch Labs Cat# 712-035-153, RRID:AB_2340639 ) HRP-conjugated secondary antibodies. Chemiluminescent signal was captured using ImageQuant LAS4000 reader (GE Healthcare, RRID:SCR_014246 ).…”
Section: Methodsmentioning
confidence: 99%
“…The etiology of PRPF8 -linked RP, comprises nearly two dozen of heterozygous genetic variants (De Erkenez et al, 2002; McKie et al, 2001; Ruzickova and Stanek, 2017) with predominance of missense mutations clustering to very C-terminus of PRPF8 that is responsible for the SNRNP200 modulation (Mozaffari-Jovin et al, 2013). Functional screens demonstrated that the majority of aberrant PRPF8 proteins exhibited altered ability to interact with spliceosome cofactors in human cell culture and impacted development including eye development in fly (Malinova et al, 2017; Stankovic et al, 2020). The only exception was the PRPF8 p.Tyr2334Asn substitution.…”
Section: Introductionmentioning
confidence: 99%
“…The only exception was the PRPF8 p.Tyr2334Asn substitution. This variant displayed in in vitro assays selective disruption of splicing efficiency and affected strongly pupation in Drosophila, but in contrast to the other pathological PRPF8 variants the PRPF8-Y2334N protein was properly incorporated into small nuclear ribonucleoprotein particles (snRNPs), key components of the spliceosome (Malinova et al, 2017; Stankovic et al, 2020). In addition, several RP-linked mutations in PRPF8 target codons at the very 3’ end of the PRPF8 coding sequence causing shortening or aberrant prolongation of the PRPF8 C-terminus (De Erkenez et al, 2002; Martinez-Gimeno et al, 2003; McKie et al, 2001; Tiwari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation